Superhard phases of simple substances and binary compounds of the B-C-N-O system: from diamond to the latest results (a Review) - Kurakevych, O. O. (Journal of superhard materials, 2009)
The basic known and hypothetic one- and two-element phases of the B-C-N-O system (both superhard phases having diamond and boron structures and precursors to synthesize them) are described. The attention has been given to the structure, basic mechanical properties, and methods to identify and characterize the materials. For some phases that have been recently described in the literature the synthesis conditions at high pressures and temperatures are indicated.